Displaying cities: museum space as a presentational device. (2nd January 2016) - Tzortzi, Kali
Abstract: Today the relation between the museum and the city becomes increasingly significant from both socioeconomic and architectural points of view. This paper examines one aspect of this relation: how the museum interior, through its physical and spatial form, can bring the city of which it is a part into its display and express its history. It takes selected European museums and, through architectural description, and spatial analysis using the concepts of sequence and choice, connectivity and depth, permeability and visibility, and axiality and convexity, shows the potential of the museum itself as a presentational device. Each case highlights a different expression of this: viewers experience the topography of the ancient city through moving in museum space, or perceive the contemporary urban landscape as the reality against which to co-ordinate the display; they engage emotionally with intangible urban meanings through the sensory qualities of architecture, or relate to the real ancient built environment through technologically mediated experiences. In all cases, acute spatial awareness of the visually immediate—either of the city itself or its spatial representation in the museum—is the condition for understanding and meaning-making, as cognitive learning and interpretation are complemented by embodied forms of knowledge, immersive experiences, and affective engagement. Using bodily movement as the primary interaction between museum and visitor, and presenting "the past as a field of experience", relates, it is argued, to the late twentieth century turn towards "affective history", and opens up new possibilities in mediating our relationship with the urban past.